Linder effect in trade disputes? An empirical research - Goh, Nathanael Hau Chien (2018)
Although there are numerous literatures that investigate the determinants of trade disputes, there are still no research done to determine if there is a possible Linder effect in bilateral trade disputes. Using a panel dataset of 174 countries between the period from 1995 to 2007, this paper aims to address this question. Through our research, we found that bilateral income asymmetry is statistically significant and has a negative effect on bilateral trade disputes which suggest that there is Linder effect in bilateral trade disputes. We are still able to arrive at the same result even after conducting various robustness checks to address some of the concerns that may affect the validity of our findings.